2019
DOI: 10.1002/mnfr.201801219
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll Supplementation in Early Life Prevents Diet‐Induced Obesity and Modulates Gut Microbiota in Mice

Abstract: Scope: The high rates of overweight and obesity, currently occurring in children, underline the urgent need for preventive strategies in early life before excess weight is gained. Methods and results: In this study, the alleviating obesity property of chlorophyll supplementation in early life is investigated using a 4-week-old C57BL/6J male mice model with obesity induced by high-fat diet (HFD). The present study finds that chlorophyll supplementation in early life can effectively retard body weight gain, impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
38
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 39 publications
(53 reference statements)
5
38
1
Order By: Relevance
“…It could be improved by the intervention of prebiotic and some plant compounds, which contributed to the alleviation of inammation, insulin resistance, and obesity. 34,36 Consistent with the previous studies, the protective effect of CSP on diet-induced obesity might be via the promotion of this benecial gut bacteria. Moreover, a distinct increase in Lactobacillus, which is also positively correlated with obesity, was independently discovered in the CSPH groups.…”
Section: Discussionsupporting
confidence: 87%
“…It could be improved by the intervention of prebiotic and some plant compounds, which contributed to the alleviation of inammation, insulin resistance, and obesity. 34,36 Consistent with the previous studies, the protective effect of CSP on diet-induced obesity might be via the promotion of this benecial gut bacteria. Moreover, a distinct increase in Lactobacillus, which is also positively correlated with obesity, was independently discovered in the CSPH groups.…”
Section: Discussionsupporting
confidence: 87%
“…Most studies used male mice to construct high-fat diet-induced obesity model [ 12 , 65 , 66 ]. In the study, we used female mice in order to discover different outcomes in males based on their different hormonal profile.…”
Section: Discussionmentioning
confidence: 99%
“…A previous animal study demonstrated that chlorophyll supplementation (0.18 mg/10 g body weight/day) could also exert beneficial effects against obesity by the decrease of body weight gain, the improvement of glucose tolerance and the reduction of low-grade inflammation in HFD-fed C57BL/6 J male mice [ 50 ]. These effects could be due to the preventive action of chlorophyll supplementation on gut dysbiosis, characterized by the decreased Firmicutes/Bacteroidetes ratios, the increased abundance of Blautia bacteria, and the significant decrease of Lactococcus and Lactobacillus bacteria [ 50 ].…”
Section: Discussionmentioning
confidence: 99%